Efforts to prevent inter-religious intolerance in Indonesia through the wise use of social media - Habibah, Siti Maizul; Ihsan; Rumiati, Sri; Gomez, Abigail (Digital Theory, Culture & Society, 2025)
The term interfaith harmony is synonymous with the term tolerance. Harmony is a term filled with the meaning of good and peace. The point is to live together in society with one heart and agree not to create disputes and fights. Living in harmony is everyone's dream. Differences on the one hand can be a strength if managed properly and professionally. However, if not, differences in worldviews between multicultural countries will become a factor in national disintegration and prolonged conflict. This article aims to find out the strategy for building religious harmony in Indonesia. The method used in this research is library research, namely tracing books and findings from interfaith harmony studies. The results of this study explain that there are 6 strategies that can be carried out in building harmony between religious communities, namely internalizing tolerance, maintaining kinship (ukhuwah), mutual respect and appreciation, mutual trust and avoiding prejudice, clarifying and confirming the information obtained and acting fairly.